A broadband UV-visible photodetector based on a Ga2O3/BFO heterojunction. (27th September 2021) - Ma, Guoliang; Jiang, Weiyu; Sun, Weiming; Yan, Zuyong; Sun, Bingyang; Li, Shan; Zhang, Maolin; Wang, Xia; Gao, Ang; Dai, Jie; Liu, Zeng; Li, Peigang; et al.
Abstract: In this work, a well-operated broadband UV-visible photodetector based on a Ga2 O3 /BiFeO3 (Ga2 O3 /BFO) heterojunction is fabricated and characterized. Under the ultraviolet (UV) light illumination with an intensity of 100 μ W·cm −2 at 254 nm in UVC waveband, at a biasing voltage of 2 V, an ultra-low dark current (I dark ) of 0.12 pA, a high photo-to-dark current ratio (PDCR) of 1.0 × 10 5, a responsivity (R) of 12.0 mA·W −1, a specific detectivity (D*) of 6.1 × 10 12 Jones, an external quantum efficiency (EQE) of 5.9%, and a UVC/visible rejection ratio ( R 235 /R 600 ) of 4.47 × 10 3 are achieved. In addition, the rise time and decay time are 0.25 s and 0.04 s, respectively. Meanwhile, the potential of the device as a self-powered photodetector is proved, and the principle of energy-band diagram is analysed for the fabricated heterojunction device. The results show that the Ga2 O3 /BFO heterojunction is a potential candidate for preforming desired broadband UV-visible photodetection.